2001
DOI: 10.1109/55.962643
|View full text |Cite
|
Sign up to set email alerts
|

Device characteristics of the GaN/InGaN-doped channel HFETs

Abstract: First dc, small signal, and RF power characteristics of GaN/InGaN doped-channel heterojunction field effect transistors (HFETs) are reported. HFETs with a 1-m gate length have demonstrated a maximum drain current of 272 mA/mm, a flat around 65 mS/mm in a between 0.65 V and +2.0 V, and an on-state breakdown voltage over 50 V. Complete pinchoff was observed for a 3.5 V gate bias. Devices with a 1-m gate length have exhibited an of 8 GHz and max of 20 GHz. A saturated output power of 26 dBm was obtained at 1.9 GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…7 shows the room-temperature (300 K) 2DEG mobility as a function of carrier density for the InGaN channel heterostructures in our work as well as previously reported results. [11][12][13][14][15][16][17][19][20][21][22][23][24][25] A record highest room-temperature electron mobility of 1681 cm 2 =(V•s) is obtained in our experiment, which is far superior to the other reported results. Despite the high mobility, the 2DEG sheet density reaches 1.30 × 10 13 cm −2 and can be further improved by increasing the barrier layer thickness or the AlN mole fraction in the AlGaN barrier.…”
contrasting
confidence: 86%
See 2 more Smart Citations
“…7 shows the room-temperature (300 K) 2DEG mobility as a function of carrier density for the InGaN channel heterostructures in our work as well as previously reported results. [11][12][13][14][15][16][17][19][20][21][22][23][24][25] A record highest room-temperature electron mobility of 1681 cm 2 =(V•s) is obtained in our experiment, which is far superior to the other reported results. Despite the high mobility, the 2DEG sheet density reaches 1.30 × 10 13 cm −2 and can be further improved by increasing the barrier layer thickness or the AlN mole fraction in the AlGaN barrier.…”
contrasting
confidence: 86%
“…[13][14][15][16] Previous reports have shown that devices with an InGaN channel exhibit excellent performance by some measures, such as suppression of current collapse and the virtual gate effect. [17][18][19][20] However, even though InGaN channel HEMTs have been manufactured and good highfrequency performance has been demonstrated, 21,22) the carrier mobility of heterostructures with an InGaN channel is still very low, less than 1295 cm 2 =(V•s) in published studies. [11][12][13][14][15][16][17][19][20][21][22][23][24][25] As discussed in previous reports, the main issues limiting the carrier mobility of InGaN channel heterostructures are alloy disorder and interface roughness scattering, which are due to the poor quality of the InGaN ternary material and the rough interface morphology between the barrier and channel layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…InGaN material has proved its potential for the realization of blue-green light-emitting diodes and laser diodes. [1] Owing to the large carrier sheet density attainable and relatively high saturation velocity, the heterojunction field effect transistors (HFETs) using InGaN alloys as channels layer promise in high-frequency and large-power fields. Furthermore, the relatively small bandgap of InGaN materials conduces to enlarging the discontinuity of conduction band and leads to better carrier confinement in the quantum well.…”
Section: Introductionmentioning
confidence: 99%
“…Some achievements have been obtained in demonstrating the outstanding properties of InGaN channel heterostructures and devices. [15][16][17][18] However, from the epitaxial point of view, it is still a challenge to obtain high-quality InGaN channel according to the state-of-the-art epitaxial technology. The main issues are the phase separation [19] and composition inhomogeneity, resulting from unfavorable thermodynamic reactions.…”
Section: Introductionmentioning
confidence: 99%